Environmental degradation and radical solution from Islamic perspective - Ahmad Munawar Ismail,; Mohd Farhan Firas, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Global warming, driven by increased greenhouse gases, primarily from human activities, poses significant challenges to weather patterns, ecosystems, and human well-being, necessitating urgent action to mitigate its impact. Proposed solutions include transitioning to sustainable energy, promoting clean technologies, raising awareness, and conserving forests. Enhanced global cooperation, climate policies, and sustainable lifestyles are crucial in this endeavor. Employing content and document analysis, this article examines the Islamic approach to tackling global warming. Islamic teachings emphasize human responsibility as stewards of the Earth, advocating for environmental preservation and conservation. This includes utilizing sustainable energy sources and preventing wastefulness. Islamic principles align with environmentalist perspectives, emphasizing sustainable urban planning, energy efficiency, and innovative research to reduce emissions and restore ecological balance. These measures mitigate global warming, reducing reliance on fossil fuels, enhancing air quality, and supporting human health. Climate awareness fosters global cooperation and collective responsibility for future generations. Integrating Islamic values into environmental efforts contributes to a holistic approach to addressing climate change, promoting harmony between humans and nature while ensuring the sustainability of our planet for generations to come.